Paradoxical effects of DNA tumor virus oncogenes on epithelium-derived tumor cell fate during tumor progression and chemotherapy response - Jiang He (Nature Publishing Group, 2021)
Abstract Epstein-Barr virus (EBV) and human papillomavirus (HPV) infection is the risk factors for nasopharyngeal carcinoma and cervical carcinoma, respectively. However, clinical analyses demonstrate that EBV or HPV is associated with improved response of patients, although underlying mechanism remains unclear. Here, we reported that the oncoproteins of DNA viruses, such as LMP1 of EBV and E7 of HPV, inhibit PERK activity in cancer cells via the interaction of the viral oncoproteins with PERK through a conserved motif. Inhibition of PERK led to increased level of reactive oxygen species (ROS) that promoted tumor and enhanced the efficacy of chemotherapy in vivo. Consistently, disruption of viral oncoprotein-PERK interactions attenuated tumor growth and chemotherapy in both cancer cells and tumor-bearing mouse models. Our findings uncovered a paradoxical effect of DNA tumor virus oncoproteins on tumors and highlighted that targeting PERK might be an attractive strategy for the treatment of NPC and cervical carcinoma.